The Latin American Publishing Circuit in the 21st Century: Following the Trajectory of César Aira - Riveiro, María Belén (2021)
This essay poses a question about the identity of Latin American literature in the 21st century. In the 1960s and 1970s, the Latin America Boom received recognition both locally and internationally, becoming the dominant means of defining Latin American literature up to the present. This essay explores new ways to understand this notion of Latin America in the literary scene. The case of the Argentine writer César Aira is relevant for analyzing alternative publishing circuits that connect various points of the region. These publishing houses foster a defiant way of establishing the value of literature.